HUKUM MENJATUHKAN TALAK DILUAR DAN DIDALAM PERADILAN: Studi Naskah Kitab Fiqih Syafi’iyah - Misnanto Misnanto (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The Essence of marriage certainly wants to be of forming a sakinah mawahdah warahmah family, divorce the key to opening the marriage bond through the courts whose job to examine, decice and adjudicate, In Indonesia, many divorces are not registered for years, usually the register when certain matters arise, this study aims to find out about how the law imposes divorce inside and outside the court according the perspective the Syafi’i Madzhab, by using the content analysis method whith the considers divorce legal in front judges with 10 catagories, namely talak: because husband’s difficulties, because causing harm to the wife, for not providing a living, due to disability, ta’asuf, due to illa’, due to li’an, due to dzhihar, duo to a postasy, this is a woman’s right to file for divorce in court when the husband does not impose divorce or indeed do not want to drop their divorce, and for divorce ta’asuf, illa’, zhihar, li’an and apostates. This is andeed the judge’s authority to dedice, but apart from divorce ta’asuf, illa’, zhihar, li’an, and apostasy. The is still lagelly punished when imposing a divorce outside the court.